Neonatal exposure of bisphenol A led to increased lipolysis of visceral adipose tissue in adult rats with DNA hypomethylation of Atgl being one of the possible underlying mechanisms. (15th May 2022) - Ke, Zhang-Hong; Yu, Ai-Li; Cai, Xue-Fen; Sun, Yan; Xu, Hui-Ling; Chen, Meng; Chen, Chen-Xi; Zheng, Bei-Hong
Abstract: Accumulating evidence suggests the role of developmental exposure of bisphenol A (BPA) in metabolic disorders. However, the underlying mechanism remains unclear. Using a rat model, we investigated the neonatal exposure of BPA on lipid metabolism in adult and the underlying mechanisms. From postnatal day1(PND1) to PND10, male rats were exposed to BPA via daily subcutaneous injection with 10 µg/100 µL BPA (1.24–0.5 mg/kg body weight/day, a dose below the US-EPA LOAEL). After fasting for 8 h, adult rats aged 80 days showed elevated levels of serum free fatty acid (FFA), glycerol and glucose, and increased levels of FFA and glycerol in visceral adipose tissue. The expression levels of key enzymes of lipolysis, adipose triglyceride lipase (Atgl) and hormone-sensitive lipase (Hsl), were increased in visceral adipose tissue from BPA-exposed rats after fasting. On the other hand, transcription levels of lipogenic genes remained unchanged. Differentiation of visceral adipocyte in rats takes place neonatally. In our study, neonatal BPA exposure induced DNA hypomethylation of Atgl in visceral adipose tissue. In 3T3-L1 cell, administration of 10 −7 mol/L BPA throughout the differentiation stage led to DNA hypomethylation and increased expression of Atgl. Our results suggest that neonatal exposure of BPA led to increased lipolysis of visceral adipose tissue in young adults, which will predispose individuals to multiple metabolic disorders. The DNA hypomethylation of Atgl might be one of the mechanisms underneath the long-lasting effect of neonatal BPA exposure.